1989
DOI: 10.1126/science.243.4897.1481
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Allatotropin from Adult Manduca Sexta

Abstract: A peptide that strongly stimulates the secretion of juvenile hormone from corpora allata in vitro (allatotropin) has been purified from extracts of heads of pharate adult Manduca sexta. The primary structure of this 13-residue peptide has been determined: H-Gly-Phe-Lys-Asn-Val-Glu-Met-Met-Thr-Ala-Arg-Gly-Phe-NH(2). This neurohormone has no sequence similarity with any known neuropeptide from other organisms. Synthetic allatotropin, as well as truncation fragments, including one with the five amino terminal res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
226
0
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 338 publications
(246 citation statements)
references
References 13 publications
13
226
0
4
Order By: Relevance
“…AT was first isolated from M. sexta as a factor that stimulates the synthesis of JH in the CA (Kataoka et al 1989). Previously, we have reported that the CA of a newly emerged A. aegypti female needs to be exposed to AT before it is capable of synthesizing JH (Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AT was first isolated from M. sexta as a factor that stimulates the synthesis of JH in the CA (Kataoka et al 1989). Previously, we have reported that the CA of a newly emerged A. aegypti female needs to be exposed to AT before it is capable of synthesizing JH (Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Allatostatins (AS) and allatotropins (AT) are structurally diverse peptides that were first described as modulators of juvenile hormone (JH) biosynthesis in the corpora allata (CA) of a number of insect species (Kataoka et al 1989;Woodhead et al 1989;Kramer et al 1991;Lorenz and Hoffmann 1995;Gilbert et al 2000). AS and AT have subsequently been recognized as having multiple physiological effects, controlling processes such as heart rate and gut motility, nutrient absorption, migratory preparedness, and modulation of the circadian cycle (Bendena et al 1999;Nässel 2002;Petri et al 2002;Elekonich and Horodyski 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13.3.91, kindly provided by Dr. J. Veenstra, University of Bordeaux, Talence, France; Veenstra and Hagedorn, 1993). The antiserum recognizes Mas-AT (Kataoka et al, 1989) and Locusta myotropin (Veenstra and Hagedorn, 1993), both ending with TARGFamide. Specificity of the anti-Mas-AT antiserum has been shown by preadsorption of the antiserum with 100 lM synthetic Mas-AT (Bachem, Bubendorf, Switzerland) for 1 h at room temperature, which abolished all immunostaining in M. sexta brain sections (data not shown).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…Mas-allatotropin, an amidated tridecapeptide (GFKNVEMMTARGF-NH 2 ) was isolated from heads of pharate adults of M. sexta (Kataoka et al, 1989). Since then, allatotropins (-TARGFamides) have been shown to be a highly conserved insect neuropeptide family (for reviews see Elekonich and Horodyski, 2003;Homberg et al, 2004;Nässel and Homberg, 2006).…”
Section: Introductionmentioning
confidence: 99%